Study of UV-B Mutation Effect on pH Resistance and Lipid Production of Microalgae Botryococcus braunii - Prastiwi, Thea; Rachma, Fanina Aulia; Aparamarta, Hakun Wirawista; Widjaja, Arief (IPTEK The Journal for Technology and Science, 2025)
Microalgae Botryococcus braunii is a potential biodiesel producer as an alternative for fossil fuels due to its high lipid content. UV-B mutations were carried out to see the effect in microalgae growth at various pHs (3-8). Reduction of nitrogen levels was carried out to see the effect on the growth and lipid production of microalgae. UV-B mutation increased the ability of growth and resistance of B. braunii against low pH. Under low nitrogen conditions, the growth of B. braunii cells would not continue for a longer time. B. braunii which grow in nitrogen depletion medium produced lipid content greater than normal nitrogen. UV-B light mutation also increased the lipid content of B. braunii. At 7 days of incubation, the mutation not only increased lipid content, but also significantly increased the TAG content of B. braunii lipids.